Single-Stage Clipping of Seven Intracranial Aneurysms in the Anterior Circulation via Unilateral Pterional Approach: A Case Report and Literature Review - Xu, Kan; Hou, Kun; Xu, Baofeng; Guo, Yunbao; Yu, Jinlu (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2020)
The occurrence of multiple intracranial aneurysms (MIAs) is not rare, with a reported incidence of 15 to 35%. However, patients harboring seven or more intracranial aneurysms are so uncommon that only sporadic cases have ever been reported. We present a rare case with seven intracranial aneurysms (two anterior communicating artery aneurysms, two right middle cerebral artery aneurysms, two left ophthalmic artery aneurysms, and one right ophthalmic artery aneurysm) in the anterior circulation that were simultaneously clipped via the extended right pterional approach. The surgery was uneventful. The patient experienced a rapid postoperative recovery with no neurologic deficits. To our knowledge, this is the first case of seven bilateral intracranial aneurysms that were surgically clipped via unilateral craniotomy. This case showed that in properly selected patients with anterior circulation MIAs, even as many as seven, one-stage clipping can be achieved. Successful clipping of the contralateral ophthalmic aneurysms was the key step in the operation.
Keywords: pterional approach; anterior circulation; multiple intracranial aneurysms; clipping